2004
DOI: 10.1097/01.gme.0000079741.18541.92
|View full text |Cite
|
Sign up to set email alerts
|

Hormone therapy and ophthalmic artery blood flow changes in women with primary open-angle glaucoma

Abstract: Although, in people with glaucoma, vasospasm can increase the risk of visual loss by inducing a retrobulbar blood flow reduction, HT seems to beneficially affect the ocular vascularization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
4

Year Published

2005
2005
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 41 publications
2
23
0
4
Order By: Relevance
“…5,6 It is well known that elevated intraocular pressure (IOP) is an important risk factor for POAG 7 and some studies indicate that supplemental estrogen plus progestin or estrogen alone in postmenopausal women reduces IOP while enhancing blood flow to the optic nerve. [8][9][10][11][12][13][14] Menopause marks a critical decline in reproductive hormones and serves as an important transition in the female reproductive aging process. POAG is unequivocally a disease where advancing age is a strong risk factor.…”
mentioning
confidence: 99%
“…5,6 It is well known that elevated intraocular pressure (IOP) is an important risk factor for POAG 7 and some studies indicate that supplemental estrogen plus progestin or estrogen alone in postmenopausal women reduces IOP while enhancing blood flow to the optic nerve. [8][9][10][11][12][13][14] Menopause marks a critical decline in reproductive hormones and serves as an important transition in the female reproductive aging process. POAG is unequivocally a disease where advancing age is a strong risk factor.…”
mentioning
confidence: 99%
“…(11,12). Additionally, animal models and clinical studies have shown that the perfusion of the optic nerve, retinal ganglion cells, and their supporting structures are increased by estradiol (13)(14)(15). Finally, estradiol has neuroprotective effect which appears to be mediated at least in part through estrogen receptors in the retinal ganglion cells in glaucoma animal models (4,13).…”
Section: Discussionmentioning
confidence: 99%
“…Another study found that HT reduced vascular resistance distal to the ophthalmic artery (OA) to levels nearly equivalent to those of pre-menopausal women [13]. Still other research has shown a significant decrease in CRA impedance after 6 [14] and 12 [15] months of HT, as well as a decrease in OA impedance after 6 months of treatment [16]. When intraocular pressure (IOP) was examined in addition to retrobulbar hemodynamics 2 months after the initiation of HT, a decrease in both IOP and the vascular resistance of the CRA and short nasal/temporal posterior ciliary arteries (NPCA/ TPCA) were noted [17].…”
Section: Introductionmentioning
confidence: 92%